Association between polymorphisms in NOBOX and litter size traits in Xiangsu pigs - Huang, Jiajin; Ruan, Yong; Xiao, Meimei; Dai, Lingang; Jiang, Chuanmei; Li, Jifeng; Xu, Jiali; Chen, Xiang; Xu, Houqiang (Frontiers in Veterinary Science, 2024)
The newborn ovary homeobox gene (NOBOX) regulates ovarian and early oocyte development, and thus plays an essential role in reproduction. In this study, the mRNA expression level and single nucleotide polymorphism (SNP) of NOBOX in various tissues of Xiangsu pigs were studied to explore the relationship between its polymorphism and litter size traits. Also, bioinformatics was used to evaluate the effects of missense substitutions on protein structure and function. The results revealed that NOBOX is preferentially expressed in the ovary. Six mutations were detected in the NOBOX sequence, including g.1624 T>C,